DYNAMIC MODELING OF RESOURCE-EFFICIENT CONSTRUCTIONS OF SAW FIBER SEPARATOR WORKING BODIES (Web of Technology: Multidimensional Research Journal, 2024)
This scientific paper modulated the dynamics of jin saw teeth, and structures in the jin working chamber to separate cotton fiber, and investigated the theoretical and practical basis for the effect of the change of working organs when modified or experimented on machine work productivity, the amount of fiber that saw speed is separated during the Jinning process.